Program of psychotherapeutic rehabilitation of internally displaced persons with psychosocial maladjustment and neurotic disorders - Halchenko Аліна (Psychosomatic Medicine and General Practice, 2021)
This is a conference abstract from the ІV Scientific and Practical Conference "Psychosomatic medicine: science and practice". It is dedicated to the program of psychotherapeutic rehabilitation of internally displaced persons with psychosocial maladjustment and neurotic disorders.